Qualification of Membrane Filtration for Planetary Protection Flight Implementation - Stott, Kristina Vaikovna; Morgan, Lyssa; Shearer, Caitlin; Steadham, Morgan Byrd; Ballarotto, Mihaela; Hendrickson, Ryan (Frontiers in Microbiology, 2022)
Planetary Protection is the practice of preventing forward and backward contamination of solar system bodies. Spacecraft and associated surfaces are sampled to ensure compliance with bioburden requirements. Current Planetary Protection sampling and processing methodologies consist of extracting microbial cells from wipe or swab samples through a procedure (NASA Standard Assay) that includes sonication, heat shock, and pour plating steps. The pour plating steps are laborious and prolonged. Moreover, results can be imprecise because only a fraction of the sample fluid is plated for CFU enumeration (80% for swabs and 25% for wipes). Thus, analysis requires that a pour fraction extrapolation factor be applied to CFU counts to account for bioburden in the remaining sample volume that is not plated. This extrapolation results in large variances for data, decreasing the accuracy of spore bioburden estimation of spacecraft hardware. In this study, we investigated the use of membrane filtration as an alternative method to pour plate processing. Membrane filtration is an appealing methodology for Planetary Protection because it can process greater sample volumes and reduces the data variance for bioburden enumeration. A pour fraction extrapolation factor is still applied for both swabs and wipes (92%), however, it is a greater pour fraction than the pour-plate method. Here we present data collected by the Jet Propulsion Laboratory and the Applied Physics Laboratory to experimentally determine the equivalency of membrane filtration to pour plate methodology for implementation during the NASA Standard Assay. Additionally, we outline the planned procedures for two membrane filtration systems: Pall® Laboratory Manifold system and Milliflex® Plus Vacuum Pump System. Both systems demonstrated equivalence of the membrane filtration method to the pour plating method.